LiDAR, UAV or compass-clinometer? Accuracy, coverage and the effects on structural models. (May 2017) - Cawood, Adam J.; Bond, Clare E.; Howell, John A.; Butler, Robert W.H.; Totake, Yukitsugu
Abstract: Light Detection and Ranging (LiDAR) and Structure from Motion (SfM) provide large amounts of digital data from which virtual outcrops can be created. The accuracy of these surface reconstructions is critical for quantitative structural analysis. Assessment of LiDAR and SfM methodologies suggest that SfM results are comparable to high data-density LiDAR on individual surfaces. The effect of chosen acquisition technique on the full outcrop and the efficacy on its virtual form for quantitative structural analysis and prediction beyond single bedding surfaces, however, is less certain. Here, we compare the accuracy of digital virtual outcrop analysis with traditional field data, for structural measurements and along-strike prediction of fold geometry from Stackpole syncline. In this case, the SfM virtual outcrop, derived from UAV imagery, yields better along-strike predictions and a more reliable geological model, in spite of lower accuracy surface reconstructions than LiDAR. This outcome is attributed to greater coverage by UAV and reliable reconstruction of a greater number of bedding planes than terrestrial LiDAR, which suffers from the effects of occlusion. Irrespective of the chosen acquisition technique, we find that workflows must incorporate careful survey planning, data processing and quality checking of derived data if virtual outcrops are to be used for robust structural analysis and along-strike prediction. Graphical abstract: Highlights: 3 virtual outcrops of the same field structure compared for accuracy and coverage. Derived from: terrestrial LiDAR, terrestrial images & UAV images. Fidelity of virtual bedding surfaces tested against compass-clinometer measurements. LiDAR-derived reconstructions of greatest accuracy, but lowest outcrop coverage. Synoptic UAV positions sample entire outcrop, improving geological predictions.